Exploring the pathogenesis of acute lung injury and its treatment through Traditional Chinese Medicine: a state-of-the-art review - Wang, Jiayun; Yan, Zhiqiang; Zhang, Xinxin; Wang, Shun; Jiao, Liangbo; Zhu, Binghua; Tan, Bo; Yang, Aidong (Frontiers in Pharmacology, 2025)
Acute Lung Injury (ALI) is a severe and progressive condition characterized by hypoxic respiratory failure, often triggered by multiple contributing factors. It is associated with high morbidity and mortality rates and can advance to Acute Respiratory Distress Syndrome (ARDS) in severe cases. The pathogenesis of ALI involves a complex interplay of pathological mechanisms, including immune-inflammatory responses, disruption of the alveolar-capillary barrier, damage to mesenchymal stem cell organelles, metabolic dysregulation, ferroptosis, and alterations in gut microbiota. From the perspective of Traditional Chinese Medicine (TCM), the development of ALI is primarily attributed to the invasion of toxic pathogens, which result in lung dysfunction. TCM treatment strategies, which emphasize heat-clearing, detoxification, promoting blood circulation, and resolving stasis, have demonstrated promising clinical efficacy. This paper provides a comprehensive analysis of the pathogenesis of ALI and explores the therapeutic mechanisms of TCM compounds and bioactive monomers with potential therapeutic benefits. The goal is to establish a solid theoretical foundation for the clinical application of TCM in ALI treatment and to further validate its scientific rationale.